Quantification of creatine kinase reaction rate in mouse hindlimb using phosphorus-31 magnetic resonance spectroscopic fingerprinting - Kim, Kihwan (NMR Biomed, 2020)
The goal of this study was to evaluate the accuracy, reproducibility, and efficiency of a (31)P magnetic resonance spectroscopic fingerprinting ((31)P-MRSF) method for fast quantification of the forward rate constant of creatine kinase (CK) in mouse hindlimb. The (31)P-MRSF method acquired spectroscopic fingerprints using interleaved acquisition of phosphocreatine (PCr) and γATP with ramped flip angles and a saturation scheme sensitive to chemical exchange between PCr and γATP. Parameter estimation was performed by matching the acquired fingerprints to a dictionary of simulated fingerprints generated from the Bloch-McConnell model. The accuracy of (31)P-MRSF measurements was compared with the magnetization transfer (MT-MRS) method in mouse hindlimb at 9.4 T (n = 8). The reproducibility of (31)P-MRSF was also assessed by repeated measurements. Estimation of the CK rate constant using (31)P-MRSF (0.39 ± 0.03 s(−1)) showed a strong agreement with that using MT-MRS measurements (0.40 ± 0.05 s(−1)). Variations less than 10% were achieved with 2 min acquisition of (31)P-MRSF data. Application of the (31)P-MRSF method to mice subjected to an electrical stimulation protocol detected an increase in CK rate constant in response to stimulation-induced muscle contraction. These results demonstrated the potential of the (31)P-MRSF framework for rapid, accurate, and reproducible quantification of the chemical exchange rate of CK in vivo.